How did Markets and Public Sentiment React During Demonetization? Study of a Significant Event in the Indian Economy - Manish Sinha; Dipasha Sharma; Pratima Amol Sheorey (Australasian Accounting, Business and Finance Journal, 2022)
The present study aims to determine the impact of shock of demonetization which happened in November 2016 in India. It has been observed in literature that while the market moves due to unforeseen events, market movements are largely affected by news reports on such events. Considering these two threads and the association between them, the study follows mixed method research methodology and assesses the impact of demonetization on stock market movement through time series analysis and text analytics of news items generated during the period. This study examines, through time series analysis, the impact of demonetization as an unexpected event on stock market movement. Time series analysis evaluates the impact on overall stock market movements and on sectoral indices, liquidity shocks in the emerging Indian economy due to demonetization. This study integrates time series analysis with robustness tests and follows text analytics, news analytics and sentiment analytics to gauge public sentiment (influenced by media coverage) during the event. These evaluations validate negative movements in the market and most of the sectors due to the negative sentiment of people about demonetization.
Keywords: Demonetization; Market Volatility; Liquidity shock; Public Sentiments; Indian Economy; Event Study